2011
DOI: 10.1007/s11746-011-1774-3
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Fatty Acid Composition of Monoglycerides and Shear on the Polymorph Behavior in Water‐in‐Palm Oil‐Based Blend

Abstract: Effect of the fatty acid composition of monoglycerides and shear on the polymorphic behavior in a water-in-oil (W/O) emulsion semi-solid fats blend was investigated. The bulk fat blend and the W/O emulsion fat blend with added either unsaturated or saturated monoglycerides were prepared using a rapid cooling heat exchanger, and the polymorphic transitions from b 0 to b-form during storage were compared by X-ray diffraction. The peak intensity of the b-polymorph of the samples with added saturated monoglyceride… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 21 publications
2
15
0
Order By: Relevance
“…The size of granular crystals in Sample 2 increased rapidly from Day 3 to 1 week, and this period corresponded to the period in which the β/β’ ratio increased. The behavior observed in this study was similar to the previous report (Shiota et al, ). We suggested that the state change of POO associated with repeatedly melting and solidifying during thermal thawing involved the polymorph transition of POP.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…The size of granular crystals in Sample 2 increased rapidly from Day 3 to 1 week, and this period corresponded to the period in which the β/β’ ratio increased. The behavior observed in this study was similar to the previous report (Shiota et al, ). We suggested that the state change of POO associated with repeatedly melting and solidifying during thermal thawing involved the polymorph transition of POP.…”
Section: Resultssupporting
confidence: 93%
“…These results suggested that POO promotes β‐type crystal formation. Shiota et al () suggested that granular crystals are more likely to be produced in mixtures in which the proportion of β‐type crystals gradually increases during storage (Shiota et al, ). The size of granular crystals in Sample 2 increased rapidly from Day 3 to 1 week, and this period corresponded to the period in which the β/β’ ratio increased.…”
Section: Resultsmentioning
confidence: 99%
“…The non-uniformly Needles: crystals with primary bonds, platelets: crystals with secondary bonds, gray needles and platelets, b and e: melting crystals with primary and secondary bonds at a higher temperature, wavy fragments: crystals with transitioning to the β-form, gray background: oil. ing in bulk fat blend based on palm oil (Shiota et al, 2011). This is consistent with the effect of lab-scale compression or shearing in the present study.…”
Section: Time Dependence Of Polymorph Transformation Of Fat Blend Witsupporting
confidence: 92%
“…The study of fat crystallization under shear was initiated half a century ago, as we described earlier . Since this review, detailed work on natural fats has been reported by many researchers . These studies clearly demonstrate that applying shear increases the rates of polymorphic crystallization and transformation of lipids, and modifies the aggregation of nanocrystals of the crystal network.…”
Section: Effects Of External Factorsmentioning
confidence: 80%